A Multilevel Approach for Social Transformations and its Implications on Service Design Education. (28th July 2017) - Morelli, Nicola; Götzen, Amalia De
Abstract : Abstract: This paper is looking at two parallel transformations -in the methodological approach to service design and in the way new social initiatives are designing new solutions – to suggest a framework to re-organise service design education. The paradigmatic framework for the service design discipline is shifting from a methodological approach that qualified services as "what is not a product" to a new approach that moves the control over the value creation process from designers and producers to the interaction among a constellation of stakeholders. Together with this shift, a parallel transformation can be observed in society, with the emergence of new organisational forms, based on collaboration, P2P and sharing concepts, which have a disruptive power over the existing social and economic system. The new initiatives, are often promoted and controlled by citizens, users or constellation of stakeholders and are framed in production/business models that do not refer to the value-chain model that inspired the industrial paradigm. Both those transformations are challenging the discipline of service design and in particular service design education, because it calls for a perspective shift, from a normative perspective, in which the designer (and consequently the service provider) was deciding modes and characteristics of value creation, to a perspective in which the designer/service provider is simply mediating the process of co-creation by generating means that support social transformation. This paper will propose a framework of new competences and tools that are being developed in design education and research, in order to address the different levels of this structure.